The role of firm performance towards sukuk financing / Adam Hamizan Ahmad Marzuki - Ahmad Marzuki, Adam Hamizan (2021)
The aim of this research is to assess the output of the role of firm performance towards sukuk financing. The study was using quantitative method to gather all the data from Thomson Reuters, Bank Negara Malaysia, Bursa Malaysia and etc. Sukuk is the dependent variable used to perform the analysis, while the independent variables used are Size (Log of Total Asset), Leverage Ratio (Debt to Total Asset), Asset Structure (measured as net plants, property and equipment divided by total assets), Profitability Ratio (Net Income to Total Asset) and company growth (Growth Rate of Total Asset). The panel data is used for companies' commitment to social capital, while the likelihood to choose sukuk represents ethical financing based on 5 years data selected from 2015 2019 in evaluating the relation between dependent and independent variables using the regression method. Based on findings, Size (Log of Total Asset), Leverage Ratio (Debt to Total Asset) and Asset Structure (measured as net plants, property and equipment divided by total assets) have significant impact on the propensity to issue sukuk. In addition, the results show little evidence to support that the Profitability Ratio (Net Income to Total Asset) and company growth (Growth Rate of Total Asset) influence the likelihood of choosing sukuk. Thus, the success of sukuk financing indicates that these factors efficiency throughout the years.